Ukhuwah Islamiyah Envelops the Life of the Mesjid Village Community Amidst the Difference Between the Muhammadiyah Community and the NU Community - Zulfah Hannum Bahri; Heny Trie Dina Aliya; Sallimah Zarli Lubis; Farhan Sauqi Abdi Harahap (MAQOLAT: Journal of Islamic Studies, 2023)
Kelurahan Masjid is one of the strategic locations in the spread of Islamic dakwah because of its strategic location in the middle of the city.  The Mosque Community with different organizational backgrounds, namely Muhammadiyah and NU, worship in four different mosques, but all four are active mosques in the field of organization, namely: Raya Al Maksum Mosque Medan, Taqwa Muhammadiyah Mosque of Mahkamah, Ar Raudha Mosque and An Nazhafah Mosque  .  The majority of the people who cover the environment are Muhammadiyah people.  The Muhammadiyah community in that environment tends to carry out worship activities at the Taqwa Muhammadiyah Mosque of Mahkamah.  Likewise with the NU community who carry out worship activities at the Ar Raudha and An Nazhafah Mosques.  At first the Kelurahan Masjid community was quite homogeneous because there was only one ideology of Muhammadiyah.  Only then did Nahdatul Ulama appear.  Since the emergence of Nahdatul Ulama, the community which was originally a homogeneous society, then there has been a transition to become a heterogeneous society so that there was a categorization of NU and Muhammadiyah and even had conflicts even though it was only in the form of criticism.